Feasibility, Acceptability, and Behavioral Outcomes from a Technology-enhanced Behavioral Change Intervention (Prostate 8): A Pilot Randomized Controlled Trial in Men with Prostate Cancer - Kenfield, Stacey A.; Van Blarigan, Erin L.; Ameli, Niloufar; Lavaki, Emil; Cedars, Benjamin; Paciorek, Alan T.; Monroy, Cynthia; Tantum, Lucy K.; Newton, Robert U.; Signorell, Coralie; Suh, Jung H.; Zhang, Li; et al. (European urology, 2019)
Increasing evidence suggests that lifestyle factors may decrease the risk of prostate cancer progression. Lifestyle guidelines and tools may support lifestyle modification after diagnosis. To determine the feasibility and acceptability of a digital lifestyle intervention among men with prostate cancer. A 12-wk pilot randomized controlled trial among 76 men with clinical stage T1–T3a prostate cancer. Eligibility included Internet access, no contraindications to aerobic exercise, and engaging in four or fewer of eight targeted behaviors at baseline. Website, Fitbit One, and text messaging to facilitate adoption of eight behaviors: vigorous activity, smoking cessation, and six diet improvements. Our primary outcomes were feasibility and acceptability based on recruitment and user data, and surveys, respectively. Secondarily, we evaluated the change in eight lifestyle behaviors, and also objective physical activity. Each factor was assigned one point, for an overall “P8 score” (range 0–8). Analysis of covariance (ANCOVA) was conducted. Exploratory outcomes included quality of life, anthropometrics, and circulating biomarkers after 12wk, and behaviors after 1yr. At baseline, men in both arms met a median of three targeted behaviors. Sixty-four men (n=32 per arm) completed the study; 88% completed 12-wk assessments (intervention, 94%; control, 82%). Intervention participants wore their Fitbits a median of 82d (interquartile range [IQR]: 72–83), replied to a median of 71% of text messages (IQR: 57–89%), and visited the website a median of 3d (IQR: 2–5) over 12wk. Median (IQR) absolute changes in the P8 score from baseline to 12wk were 2 (1, 3) for the intervention and 0 (−1, 1) for the control arm. The estimated mean score of the intervention arm was 1.5 (95% confidence interval: 0.7, 2.3) higher than that of the control arm at 12wk (ANCOVA p<0.001). Changes were driven by diet rather than exercise. Limitations include self-reported diet and exercise data. Overall, in this novel pilot trial, the intervention was feasible and acceptable to men with prostate cancer. Next steps include improving the intervention to better meet individuals’ needs and focusing on increasing physical activity in men not meeting nationally recommended physical activity levels. Tailored print materials combined with technology integration, including the use of a website, text messaging, and physical activity trackers, helped men with prostate cancer adopt healthy lifestyle habits, in particular recommended dietary changes, in the Prostate 8 pilot trial. Tailored print materials combined with technology integration, including the use of a website, text messaging, and physical activity trackers, helped men with prostate cancer adopt healthy lifestyle habits, in particular recommended dietary changes, in the Prostate 8 pilot trial.